Jisshūnen kinen hatenkō saishin'an undō kyōgi taikai - Yokota, Tōsui; Matsuno, Sōfū (Tōkyō : Dai Nihon Yūbenkai, 1923)
The board game depicts images of boys playing a few different kinds of sports.
Title from the print. Published as supplement to a boys magazine, titled, 'Shōnen kurabu', to comemorate the 10th year of the publication.
Keywords: Sports -- Japan -- Pictorial works; Boys -- Japan -- Pictorial works; Sugoroku (Game); Board games -- Japan